2020
DOI: 10.3390/sym12010148
|View full text |Cite
|
Sign up to set email alerts
|

Micromagnetorotation of MHD Micropolar Flows

Abstract: The studies dealing with micropolar magnetohydrodynamic (MHD) flows usually ignore the micromagnetorotation (MMR) effect, by assuming that magnetization and magnetic field vectors are parallel. The main objective of the present investigation is to measure the effect of MMR and the possible differences encountered by ignoring it. The MHD planar Couette micropolar flow is solved analytically considering and by ignoring the MMR effect. Subsequently, the influence of MMR on the velocity and microrotation fields as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 40 publications
1
10
0
Order By: Relevance
“…Khan et al [20] recorded MHD nanofluid flow, along with non-linear radiation, through a non-linear stretching and shrinking wedge. A few relevant studies on MHD non-Newtonian fluids flow can be found in [21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…Khan et al [20] recorded MHD nanofluid flow, along with non-linear radiation, through a non-linear stretching and shrinking wedge. A few relevant studies on MHD non-Newtonian fluids flow can be found in [21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, represents a measure of the micropolar diffusion over molecular dissipation (Aslani et al. 2020).…”
Section: Resultsmentioning
confidence: 99%
“…1987 a , b ; Takashima 1996; Aslani et al. 2020). This approximation ignores the solution of the magnetic induction equation, which leads to a reduction of the equations to be solved.…”
Section: Mathematical Formulationmentioning
confidence: 99%
See 2 more Smart Citations